Conflict in the Academy - Morgan, M. author. aut Link
VIII, 96 p.
Keywords: Examining an intramural conflict that erupted within the English Faculty at Cambridge University in the early 1980s, this book develops a theoretical analysis of disputes as they unfold within the academy and explores the broader historical shifts within Higher Education and how these related to developments in Continental Europe.